Kasulis' intimacy/integrity heuristic and epistemological pluralism in nursing. (15th October 2020) - McCaffrey, Graham
Abstract: Epistemological pluralism is a recognized feature of nursing knowledge, which embraces both objective, scientific knowledge and situated knowledge that include subjective experience, values and affect, and is encountered in relationship. While there is a lively literature about describing and validating the need for pluralism in nursing's knowledge base, there has been less discussion of how to work with and across different kinds of knowing that are used in practice. In this paper, I describe Kasulis' heuristic framework for understanding more clearly what is entailed in different kinds of knowledge, and what some of their advantages and disadvantages might be. The framework was created by Thomas Kasulis, an American scholar of Japanese philosophy who identified broad orientations in Asian and Western philosophies that he characterized as 'intimacy' and 'integrity', respectively. Kasulis emphasized that his framework is a heuristic, a tool for making distinctions more clearly between different styles of thinking, that can manifest not only between cultural traditions from different parts of the world, but also between subcultures within one of the dominant orientations. He breaks his two orientations down by five distinguishing categories of objectivity, relating, affect, embodiment and transparency. In this paper, each category is described and discussed in relation to aspects of nursing knowledge. Looking at different epistemological viewpoints in this way helps to clarify their differences, and to explain the difficulty of reading across them, when they entail basic assumptions that are not commensurable with each other. Kasulis' framework offers a new way of reading across viewpoints commonly seen in the epistemological pluralism of nursing. It is a tool that can sharpen critical discernment about what is at stake, what can be gained, and what might get missed while operating in either the intimacy or integrity orientation.